Intelligent Agents in the Evolution of Web and Applications - Nguyen, Ngoc Thanh.; Jain, Lakhmi C. (Studies in Computational Intelligence, 2009)
Intelligent agents are widely used in many real world applications including the evolution of web and applications. The contributions included in the book are: Innovations in Intelligent Agents in the Evolution of Web and Applications A Multi-Agent System Based on Evolutionary Learning for the Usability Analysis of Websites Towards Norm-Governed Behavior in Virtual Enterprises e-JABAT - An Implementation of Web-based A-Team A Resource Discovery Method Based on Multi-Agents in P2P Systems Adaptive and Intelligent Agents Applied in the Taking of Decisions Inside a Web-Based Education System Browsing Assistant for Changing Pages Considering Resource Management in Agent-based Virtual Organization BDI Agents: Flexibility, Personalization and Adaptation for Web-based Support Systems Ontology for Agents and the Web Ontology Agents and their applications in the Web-based Education Systems An Evolutionary Approach for Intelligent Negotiation Agents in e-Marketplaces Security of Intelligent Agents in the Web-based Application